Effect of feeding Moringa oleifera based complete pellet feed on milk yield, composition, fatty acids, somatic cell count and cell mediated immunityin lactating goats - KUMAR, RAVINDRA; VASWANI, SHALINI; ARIF, M (The Indian Journal of Animal Sciences, 2024)
Lactation cum feeding trial was conducted on 12 female Barbari goats (Age approx. 2-3 years and mean body weight 34.72 ±1.28 kg) for 120 days after approximately one month of kidding and effect on milk production, milk constituents, somatic cell count, milk fatty acid profile and cell mediated immunity was studied. Animals were divided into two groups (Gr G and Gr M) of six each as per completely randomized design. Two types of complete pellet (Moringa oleifera and Cicer arietinum) based was formulated containing sundried Moringa biomass and Gram straw along with conventional feed ingredients. Lactating goats of Gr G was fed with gram straw based complete pellet feed while goats of Gr M was fed with Moringa based complete pellet feed. Both the complete pellet feeds were iso nitrogenous. No significant difference in body weight changes was recorded between groups. The milk production (g/day) was higher (Avg. 14.54%) in Gr M as compared to Gr G at different fortnight. No significant difference was reported in the milk composition. Milk fat, SNF, Protein and lactose was similar in both the groups. Milk Somatic cell count (×10 3/ml) was significantly (P<0.05) lower in lactating goats fed with Moringa based feed. Cell-mediated immune response assessed through delayed-type hypersensitivity (DTH) reaction against phyto haemagglutinin (PHA-P) was more pronounced in Gr M at 72 and 96 hrs.Higher concentration of unsaturated fatty acids (about 16.19%) and lower saturated fatty acids (about 5.49%) was reported in Gr M. Milk fatty acid profile indicators like Index of atherogenicity (IA) was lower while hypo/hyper cholesteremic ratio and health promoting index was higher in milk of moringa based pellet fed goats. Present study concluded that Barbari goats fed with Moringa based complete pellet feed produced higher milk yield with healthier fatty acid profile with low somatic cell counts.